Beliefs about employment of people living with psychosis - Margaret E. Hampson; Richard E. Hicks; Bruce D. Watt (Australian Journal of Psychology, 2018)
Objective This qualitative study aimed to construct knowledge about myths that may exist in relation to the employability of people living with psychosis. This article presents information about work‐related beliefs expressed by participants in a qualitative study which investigated the employment barriers and support needs of people living with psychosis. Identified beliefs were critically examined against objective evidence obtained from existing literature as well as the lived experience of participants. Method Focus groups and individual interviews were conducted with 137 participants drawn from six key stakeholder groups including people with lived experience of psychosis, employers, care‐givers, employment service providers, health professionals, and community members. Thematic analysis was used to identify perceived employment barriers and support needs of people living with psychosis. The data were explored and analysed with the assistance of NVivo 10. Results The study found that negative beliefs about the employability of people living with psychosis constituted a significant barrier to their employment. In‐depth analysis of the data identified what can be considered ten potential myths regarding the employability of people living with psychosis. The main myths are that employment is too stressful for people living with psychosis and that people living with these conditions are not interested or are incapable of working effectively in competitive employment. Conclusions The study suggests that public and professional beliefs may constitute significant barriers to the employment of people living with psychosis and may need to be challenged if people living with psychosis are to receive appropriate support to achieve their vocational goals.